Sustainable politics and the crisis of the peripheries Ireland and Greece - Leonard, Liam.; Botetzagias, Iosif (Bingley, U.K. : Emerald, 2011)
This volume of the Advances in Ecopolitics examines the impact of the economic crisis on peripheral European states such as Ireland and Greece. Following an introductory chapter, it is divided into two geographically-focussed sections, the first on Ireland, the second section on Greece. Specifically the book focuses on governance, sustainable politics and environmental policies, within the context of accelerated growth and the subsequent economic downturn. It examines issues of governance and politics within these peripheral states, in addition to the development of policies within an EU/EC context. The book concludes with a discussion of the future for sustainable politics in the peripheral states of Europe, in the aftermath of the global downturn. Advances in Ecopoliticsis essential reading for all academics, researchers and practioners who are involved in the areas of environmentalism, providing insight and extending understanding of these issues.
Introduction / Liam Leonard, Iosif Botetzagias -- ch. 1. 'The Myth of the Celtic Tiger' : the political economy of Irish development since the 1990s / Peadar Kirby -- ch. 2. Power, corruption and lies : Irish political, economic and social policy : 19002011 / Liam Leonard, Paula Kenny -- ch. 3. Sustainability and community : 'The un-sustainability of the social model of neo-liberal globalisation and the speechlessness of the community at the periphery' / Kieran Keohane, Carmen Kuhling -- ch. 4. Social partnership and the fiscal crisis in Ireland : acceptance or acquiescence? / Kieran Allen -- ch. 5. An issue history / Liam Leonard -- ch. 6. Euro's crisis : from the sovereigns to the banks and back to the sovereigns / Constantin Gurdgiev -- ch. 7. Greece and the EU : promoting the idea of sustainable development : easy to plan, hard to achieve / Tsaltas Grigoris, Rodotheatos Gerasimos -- ch. 8. Green politics in Greece at the time of fiscal crisis / Iosif Botetzagias -- ch. 9. Environmental policy in Greece reloaded : plurality, participation and the sirens of neo-centralism / Charalampos Koutalakis -- ch. 10. Social capital and environmental policies in Greece / Nikoleta Jones -- Conclusion : peripheral P.I.G.S. in the last chance saloon ... / Liam Leonard, Iosif Botetzagias.
Print version record
Keywords: Nature -- General; Nature -- Environmental Conservation & Protection; Business & Economics -- Environmental Economics; The environment; Environmentalist thought & ideology; Environmental policy -- Ireland; Environmental policy -- Greece; Sustainability -- Political aspects -- Ireland; Sustainability -- Political aspects -- Greece